'Aerobic scope protection' reduces ectotherm growth under warming. (4th June 2021) - Jutfelt, Fredrik; Norin, Tommy; Åsheim, Eirik R.; Rowsey, Lauren E.; Andreassen, Anna H.; Morgan, Rachael; Clark, Timothy D.; Speers‐Roesch, Ben
Abstract: Temperature has a dramatic effect on the physiology of ectothermic animals, impacting most of their biology. When temperatures increase above optimal for an animal, their growth gradually decreases. The main mechanism behind this growth rate reduction is unknown. Here, we suggest the 'aerobic scope protection' hypothesis as a mechanistic explanation for the reduction in growth. After a meal, metabolic rate, and hence oxygen consumption rate, transiently increase in a process called specific dynamic action (SDA). At warmer temperatures, the SDA response usually becomes temporally compressed, leading to a higher peak oxygen consumption rate. This peak in oxygen consumption rate risks taking up much of the animal's aerobic scope (the difference between resting and maximum rates of oxygen consumption), which would leave little residual aerobic scope for other aerobic functions. We propose that water‐breathing ectothermic animals will protect their postprandial residual aerobic scope by reducing meal sizes in order to regulate the peak SDA response during times of warming, leading to reductions in growth. This hypothesis is consistent with the published literature on fishes, and we provide predictions that can be tested. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.